Not Just Knowledge and Skills: Transformations in Teacher Socialization and Identity - Sakadolskienė, Emilija (Acta Paedagogica Vilnensia, 2017)
While changes in global realities require transformations in institutions, educational policy-making and in cultural contexts, another essential transformation rests upon preservice teachers as they prepare to enter the profession. One of the great challenges that lies in teacher education is in counteracting the effect of thirteen years of experiences in classrooms (what Dan Lortie calls the “apprenticeship of observation”) if we want teachers not to teach the way they were taught. Earlier literature focuses on teacher socialization – the process by which an individual becomes a participating member of the teacher community (Lortie 1975; Danziger 1971; Schempp & Graber 1992), which is often a contest between societal expectations and individual inclinations of preservice teachers. Later research focuses on teachers’ professional identity formation and the identification and presentation of professional identity characteristics (Beijaard, Meijer & Verloop 2004; Lasky 2005; Flores & Day 2006), focusing on how teachers define themselves to themselves and others. Teacher identity is constructed through experiences that affirm what it means to teach. If done mindfully, this is a difficult, intricate process that takes considerable time and effort. Many researchers point to the mismatch between graduating students’ perceptions of themselves in teaching and the “praxis shock” (Harlow & Cobb 2014) that occurs when they enter the profession. In this theoretical review of literature, implications from multinational examples will be explored to inform the reform efforts in Lithuanian teacher education.